2002
DOI: 10.1111/1528-3577.00096
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Creation of a New International Human Rights Treaty: Active Learning in the International Studies Classroom

Abstract: This article details a simulation of formulating a new international human rights treaty designed for an introductory international studies course. Student understanding and interest in a range of international relations topics-including diplomacy, two-level games, international law, human rights, and group decision making-are reinforced by actively engaging the students in policy formulation and state-to-state negotiations. The article is structured around the four key components of active learning approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 4 publications
0
41
0
Order By: Relevance
“…Even though some researchers have noted that they may not be effective (Kille, 2002;Prince, 2004;Rochester, 2003), or that they need to be better assessed (Grosen and Washbush, 2004), the twin goals of engagement and knowledge acquisition are central to explaining the usefulness of simulations in the political science classroom (Caruson, 2005;Smith and Boyer, 1996;Wakelee, 2008), However, Frederking (2005, as well as Shellman and Turan (2006), have argued that active learning through simulations enhanced student learning and noted that their courses student learning outcomes were met and the students gained knowledge of key theories and concepts of international relations. Enterline and Jepsen (2009) have found that, when given a postsimulation semi-structured survey, the students reported high levels of satisfaction with the exercise and, more importantly, came away with a deeper understanding of concepts related to international relations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though some researchers have noted that they may not be effective (Kille, 2002;Prince, 2004;Rochester, 2003), or that they need to be better assessed (Grosen and Washbush, 2004), the twin goals of engagement and knowledge acquisition are central to explaining the usefulness of simulations in the political science classroom (Caruson, 2005;Smith and Boyer, 1996;Wakelee, 2008), However, Frederking (2005, as well as Shellman and Turan (2006), have argued that active learning through simulations enhanced student learning and noted that their courses student learning outcomes were met and the students gained knowledge of key theories and concepts of international relations. Enterline and Jepsen (2009) have found that, when given a postsimulation semi-structured survey, the students reported high levels of satisfaction with the exercise and, more importantly, came away with a deeper understanding of concepts related to international relations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simulations have been found to benefit students with differing learning styles (Brock and Cameron 1999) and to engage students in the material in ways that a traditional lecture/textbook method sometimes does not (McIntosh 2001;Kille 2002). Simulations have been found to be effective tools for both content learning and skill development (Lantis 1998), as well as means of encouraging both higher-order learning and appreciation for situational complexities (TorneyPurta 1992).…”
Section: Simulations and Political Learningmentioning
confidence: 99%
“…Clear rules of engagement matter (Asal and Blake 2006). There is a particular need for well specified and realistic learning objectives (Kille 2002;Shaw 2004). The break from the traditional and hierarchical lecture style increases student involvement but also necessitates the active management of the actual simulation in order to prevent ''social loafing'' and ''free riding.''…”
Section: Active Learning Simulation and Role-playingmentioning
confidence: 99%